Draft genome dataset of Streptomyces griseoincarnatus strain R-35 isolated from tidal pool sedimentsMendeley DataNCBI - Danielle Dana Mitchell; Jo-Marie Vreulink; Alaric Prins; Marilize Le Roes-Hill (Data in Brief)
The marine isolate, Streptomyces griseoincarnatus strain R-35, was isolated from marine sediments collected from the Glencairn Tidal Pool, Table Mountain National Park, Cape Town, South Africa. The genomic DNA was sequenced using the Ion Torrent GeneStudio™ S5 platform, and the de novo assembly was performed using the SPAdes assembler on the Centre for High Performance Computing (CHPC) Lengau Cluster located at the CSIR, Rosebank, South Africa. The draft genome assembly consisted of 722 contigs totaling 7,625,174 base pairs and a G+C% content of 72.2 mol%. Genome completeness and genome contamination were determined as 99.12% and 0.92%, respectively. Genome annotations performed using the Rapid Annotation with Subsystem Technology (RAST) and the Bacterial and Viral Bioinformatics Resource Centre (BV-BRC) determined the presence of 7996 coding sequences (CDS), 63 transfer RNAs (tRNAs), and six ribosomal RNAs (rRNAs). A total of 2570 hypothetical proteins were assigned, and 5246 proteins were assigned to function. The phylogenomic positioning of S. griseoincarnatus strain R-35 was determined using the Type Strain Genome Server (TYGS) and was found to be related to S. griseoincarnatus JCM 4381T, with a digital DNA-DNA hybridisation (dDDH) value of 84.1%, and an OrthoANIu value of 98.22%. The CARD RGI algorithm on Proksee predicted the presence of 6,107 antimicrobial resistance (AMR) features, 27 biosynthetic gene clusters (BGCs) were predicted using antiSMASH, while 189 carbohydrate-active enzymes (CAZymes) were predicted using dbCAN3. The raw genome sequencing data has been submitted to the National Center for Biotechnology (NCBI) under the BioProject ID PRJNA1129156 (BioSample ID Accession Number: SAMN42145163; Short Read Archive (SRA) Accession: SRR29633055; https://www.ncbi.nlm.nih.gov/bioproject/PRJNA1129156).